2023
DOI: 10.1186/s40942-023-00441-4
|View full text |Cite
|
Sign up to set email alerts
|

Color vision restrictions for medical school admission: a discussion on regulations in ASEAN countries compared to countries across the world

Abstract: Color vision deficiency impairs one’s ability to perceive and discriminate colors. Color-deficient individuals may face discrimination in various occupations, particularly in medical school admissions. This discussion seeks to compare the existing color vision requirements for entry to medical school in Southeast Asian countries as compared to countries across the world. Following this, we explore the published evidence in this field, to provide recommendations for future guidelines that will maximize the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However some studies showed CVD did have an impact on some professions, such as police officer [23] , doctor [24][25] . Proper guidance and some auxiliary equipment [6,[26][27][28] may help them better adapt to daily life, study and work, for example, wearing colored lenses [29] , choosing a subspecialty which is not limited by VCD, modifying the classic traffic lights for CVD patients [30] . Education workers and health workers should be educated about CVD.…”
Section: Discussionmentioning
confidence: 99%
“…However some studies showed CVD did have an impact on some professions, such as police officer [23] , doctor [24][25] . Proper guidance and some auxiliary equipment [6,[26][27][28] may help them better adapt to daily life, study and work, for example, wearing colored lenses [29] , choosing a subspecialty which is not limited by VCD, modifying the classic traffic lights for CVD patients [30] . Education workers and health workers should be educated about CVD.…”
Section: Discussionmentioning
confidence: 99%